A study of casino performance in United States - Cao, Jacqueline Shurong (2009)
The purpose of this study is to explore the effects and implications that casinos have on the economy. A total of 26 American states together with certain economic indicators were chosen for this study. The indicators selected were gaming revenues, Gross Domestic Product (GDP) and Personal Income Per Capita (PCI). Our preliminary findings suggest that affluence has positive relationship with the casino revenue, the gaming revenue is a stable contributor to the states revenue and lastly casino tend to recover faster than other industries during economic crisis. Through this study, we hope to find the relationship between Singapore Integrated Resort (IR) and Singapore’s economy. In addition, we hope to provide potential investors an overview of the casino industry.